A controlled study of the general level framework: Results of the Southof England competency study - Antoniou, S; Webb, D G; Mcrobbie, D; Davies, J G; Bates, Ian (Pharmacy Education, 2018)
Background: In consistency in the practice of clinical pharmacy at a junior level encouraged our group to develop a general level competency framework (GLF) to facilitate practitioner development and assessment. The framework consists of patient-related, personal and problem-solving clusters of competencies assessed on a four-point frequency scale. This study describes a large, controlled study to determine whether the framework could improve the clinical practice of junior hospital pharmacists. Method: One hundred and two junior grade pharmacists in 22 acute NHS trusts in the south of England were recruited. The hospitals were enrolled as either intervention (n=13; 72 pharmacists) or non-intervention sites (n=9; 30 pharmacists).The pharmacists (“tutees”) and senior supervisors (“tutors”) in the active sites used the competency framework for practice development. Tutees and tutors in the control sites did not have access to the competency framework, and measures were taken to ensure these trusts remained isolated from the assessment outcomes. All pharmacists were assessed at baseline, 3, 6and 12 months. Non-intervention pharmacists were assessed by external evaluators. Results: A repeat measures analysis (month-6 compared to baseline, month-12 compared to baseline) revealed that the intervention group showed an improvement in 24 of the 25 competencies at month-6, which was sustained at month-12. In contrast, the non-intervention pharmacists demonstrated an improvement in just 7 of the competencies at month-6 increasing to 12 competencies by month-12 (Table I). Using an aggregated competency score for each recruit, intervention and non-intervention pharmacists were compared using an application of Kaplan-Meier analysis. Event status was defined as the achievement of competence, detected by the attainment of a predefined threshold score. A significant difference existed between the groups at all time points (log rank=7.97,p=0.0048). Discussion: This controlled study demonstrates that tutees in the intervention sites improved significantly in 24 of the 25 patient-related competencies at 6 months and that this was sustained at 12 months. By contrast, non-intervention candidates showed progression in only 12 of the 25 competencies.